Peculiarities of the examination of citrus fruits (mandarins) during the forensic examination (Bulletin of Kharkiv National University of Internal Affairs, 2024)
In today’s environment, the issue of ensuring the identification and safety of imported products is of particular relevance, which is aimed at the successful functioning of the state in the global economy and the reduction of technical barriers to trade. The article discusses the peculiarities of conducting an examination of citrus fruits, in particular, tangerines, with a view to their further classification in the Ukrainian Classifier of Goods for Foreign Economic Activity.Approaches to the classification of citrus fruits in the process of commodity examination are summarized. The diagnostic tasks to be solved by the forensic expert during the study of citrus fruits are defined, which will allow to have more analytical information from this category of goods. The main identification tasks of the commodity examination of citrus fruits, in particular mandarins, are: determination of the variety or species of mandarins, detection of certain quality markers, determination of origin, assessment of the degree of freshness and maturity, detection of deviations from standards. Modern methods of analysis are indicated, which allow to carry out research on tangerines at the molecular, chemical and morphological levels in order to obtain objective information about their quality, safety and other characteristics that may be important in court proceedings. The main aspects of microbiological methods during the examination include: detection of pathogenic microorganisms (analysis for the presence of pathogenic bacteria such as Salmonella, E. coli and Listeria monocytogenes), determination of the level of the total microbial flora, assessment of the degree of rot and mold, determination of the effectiveness of preservatives and other preservation methods, assessment of compliance with food safety standards. Systematization of information data on characteristic defects of citrus fruits (tangerines), namely: rot, mold, mechanical damage, weak skin color, increased acidity, defects in shape or size (identified defects are of natural origin) is presented. Defects that are characteristic of low-quality products with signs of deterioration: rot, mold, mechanical damage, signs of drying or desiccation, heterogeneity in color and texture. The mechanism of forensic commodity examination of citrus fruits (tangerines) is described.